Financial Accounting Theory - Deegan, Craig (Australia McGraw-Hill, 2007)
Presents the various theories of financial accounting through a balanced and dynamic approach. Clearly written, this title provides comprehensive coverage of internationally developed accounting theories from a European perspective.
Include Index.
Keywords: Accounting -- Accounting--Study and teaching -- Financial statements